2019
DOI: 10.1177/0306624x19862430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gambling Disorder Among Prisoners: A Systematic Review

Abstract: Prevalence of gambling disorder among prisoners: a systematic reviewThis paper presents the first systematic review of studies on the prevalence of gambling disorder among prisoners across international jurisdictions. Only original studies which were published in English and employed reliable and valid screening tools are included in this analysis. The review finds that rates of problem or pathological gambling in prison populations are highly variable, ranging from 5.9 to 73% of male and female inmates survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Both the connection between gambling and crime and that between gambling and social disadvantage are well established. Numerous studies have found higher rates of problem gambling among criminal offenders than in the general population (Turner and McAvoy 2011;May-Chahal et al 2017;Turner et al 2017;Moore 2018;Riley et al 2018;Lind et al 2019;Widinghoff et al 2019;Banks et al 2020). Although only a relatively small proportion of all crime is gambling-related (Arthur et al 2014), a study on British prisoners estimated that problem gambling is linked with up to 13% of all offending (May-Chahal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both the connection between gambling and crime and that between gambling and social disadvantage are well established. Numerous studies have found higher rates of problem gambling among criminal offenders than in the general population (Turner and McAvoy 2011;May-Chahal et al 2017;Turner et al 2017;Moore 2018;Riley et al 2018;Lind et al 2019;Widinghoff et al 2019;Banks et al 2020). Although only a relatively small proportion of all crime is gambling-related (Arthur et al 2014), a study on British prisoners estimated that problem gambling is linked with up to 13% of all offending (May-Chahal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of recent Systematic Reviews completed in the eld of gambling, investigating a range of ideas. For example, the relationship between crime and gambling disorders 6,7 , quality of life measurement tools 8 , comorbidity with other conditions 9 , socioeconomic risk factors and vulnerable populations 10 , impulsivity in gambling 11,12 , harms reported by signi cant others 13 , or potential interventions and harm minimisation tools [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of recent Systematic Reviews completed in the eld of gambling, investigating a range of ideas. For example, the relationship between crime and gambling disorders 5,6 , quality of life measurement tools 7 , comorbidity with other conditions 8 , socioeconomic risk factors and vulnerable populations 9 , impulsivity in gambling 10,11 , harms reported by signi cant others 12 , or potential interventions and harm minimisation tools [13][14][15][16] . Despite this body of research, and many individual studies investigating speci c gambling harms, a systematic review of how harms are distributed across society hasn't yet been done.…”
Section: Introductionmentioning
confidence: 99%